Lactoferrin Decreases Enterotoxigenic Escherichia coli-Induced Fluid Secretion and Bacterial Adhesion in the Porcine Small Intestine - Matthias Dierick; Ruben Ongena; Daisy Vanrompay; Bert Devriendt; Eric Cox (MDPI AG, 2022)
Enterotoxigenic Escherichia coli (ETEC) infections are one of the most prevalent causes of post-weaning diarrhea in piglets, resulting in morbidity, mortality and elevated use of antibiotics. The emergence and further spread of antimicrobial resistance together with the growing demand for high quality animal protein requires the identification of novel alternatives for antimicrobials. A promising alternative is lactoferrin, as we previously showed that it can both inhibit the growth and degrade bacterial virulence factors of porcine ETEC strains in vitro. Aiming to confirm these findings in vivo, we performed a small intestinal segment perfusion experiment in piglets. Here, we showed that lactoferrin could not only decrease ETEC-induced fluid secretion, but also their ability to colonize the small intestinal epithelium. Furthermore, while ETEC infection induced pro-inflammatory cytokine mRNA expression in this experiment, lactoferrin was not able to counteract these responses. In addition, a bacterial motility assay showed that lactoferrin can reduce the motility of ETEC. Our findings further support the use of lactoferrin as an alternative for antimicrobials and also show its potential for the prevention of ETEC infections in pigs.